School performance, score inflation and economic geography - Erich Battistin; Lorenzo Neri (Queen Mary University of London, School of Economics and Finance, 2017)
We show that grading standards for primary school exams in England have triggered an inflation of quality indicators in the national performance tables for almost two decades. The cumulative effects have resulted in significant differences in the quality signaled to parents for otherwise identical schools. These differences are as good as random, with score manipulation resulting from discretion in the grading of randonly assigned external markers. We find large housing price gains from the school quality improvements artificially signaled by manipulation as well as lower deprivation and more businesses catering to families in local neighbourhoods. The design ensures improved external validity for the valuation of school quality with respect to boundary discontinuities and has the potential for replication outside of our specific case study.
Keywords: C26; C31; I2; 330; House prices; School quality; Score inflation